The Improving Rural Cancer Outcomes Trial: A cluster-randomised controlled trial of a complex intervention to reduce time to diagnosis in rural cancer patients in Western Australia - Emery, J.; Gray, V.; Walter, F.; Cheetham, Shelley; Croager, E.; Slevin, Terry; Saunders, C.; Threlfall, T.; Auret, K.; Nowak, A.; Geelhoed, E.; Bulsara, M.; et al. (Nature Publishing Group, 2017)
© The Author(s) named above. Background:Rural Australians have poorer survival for most common cancers, due partially to later diagnosis. Internationally, several initiatives to improve cancer outcomes have focused on earlier presentation to healthcare and timely diagnosis. We aimed to measure the effect of community-based symptom awareness and general practice-based educational interventions on the time to diagnosis in rural patients presenting with breast, prostate, colorectal or lung cancer in Western Australia.Methods:2 × 2 factorial cluster randomised controlled trial. Community Intervention: cancer symptom awareness campaign tailored for rural Australians. GP intervention: resource card with symptom risk assessment charts and local cancer referral pathways implemented through multiple academic detailing visits. Trial Area A received the community symptom awareness and Trial Area B acted as the community campaign control region. Within both Trial Areas general practices were randomised to the GP intervention or control. Primary outcome: total diagnostic interval (TDI).Results:1358 people with incident breast, prostate, colorectal or lung cancer were recruited. There were no significant differences in the median or ln mean TDI at either intervention level (community intervention vs control: median TDI 107.5 vs 92 days; ln mean difference 0.08 95% CI -0.06-0.23 P=0.27; GP intervention vs control: median TDI 97 vs 96.5 days; ln mean difference 0.004 95% CI -0.18-0.19 P=0.99). There were no significant differences in the TDI when analysed by factorial design, tumour group or sub-intervals of the TDI.Conclusions:This is the largest trial to test the effect of community campaign or GP interventions on timeliness of cancer diagnosis. We found no effect of either intervention. This may reflect limited dose of the interventions, or the limited duration of follow-up. Alternatively, these interventions do not have a measurable effect on time to cancer diagnosis.